2013
DOI: 10.1177/039463201302600327
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Atopy Patch Test on a Child with Milk Protein-Induced Enterocolitis Syndrome: A Case Report

Abstract: We describe the case of a child affected by milk-protein induced enterocolitis, in which oral challenge with corn was performed without symptoms after a negative specific Atopy Patch Test. Food protein-induced enterocolitis syndrome (FPIES) is an uncommon non-IgE-mediated gastrointestinal food hypersensitivity of infancy, characterized by severe vomiting and diarrhea arising within 1 to 3 hours after ingestion of the causative food. Little is known about the pathophysiology of FPIES. The absence of food-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Though the majority of patients with FPIES have undetectable serum IgE at the time of diagnosis, 18-30 % of FPIES patients may develop IgE mediated food sensitivity to the same food at some point during their course, with some developing immediate type symptoms of classic IgEmediated food allergy [8,24,29]. Gastric juice leukocytosis at 3 h after a food challenge and atopy patch testing with fresh foods (APT) have been investigated in FPIES patients [30][31][32][33]. However, the results are equivocal, and therefore their diagnostic utility remains unclear and they are not recommended for routine evaluation of FPIES [1,26].…”
Section: Diagnosismentioning
confidence: 99%
“…Though the majority of patients with FPIES have undetectable serum IgE at the time of diagnosis, 18-30 % of FPIES patients may develop IgE mediated food sensitivity to the same food at some point during their course, with some developing immediate type symptoms of classic IgEmediated food allergy [8,24,29]. Gastric juice leukocytosis at 3 h after a food challenge and atopy patch testing with fresh foods (APT) have been investigated in FPIES patients [30][31][32][33]. However, the results are equivocal, and therefore their diagnostic utility remains unclear and they are not recommended for routine evaluation of FPIES [1,26].…”
Section: Diagnosismentioning
confidence: 99%
“…Several studies have suggested a key role for T cells in FPIES patients, particularly by founding positive patch test or positive lymphocyte transformation test to the specific food allergen 2228. It has been suggested that secretion of proinflammatory cytokines TNF-α and IFN-γ, in combination with a relative lack of expression of TGF-β-receptors (known as a protector of the intestinal wall) may contribute to local inflammation and increased intestinal permeability 16,2931.…”
Section: Introductionmentioning
confidence: 99%
“…Хроническая форма возникает при ежедневном приеме пищи (например, кормление ребенка смесью на основе КМ или сои). Симптомы FPIES представлены перемежающейся рвотой, хронической диареей, недостаточной прибавкой веса или задержкой развития [26]. Младенцы с хроническим FPIES обычно возвращаются к своему обычному состоянию через 3-10 дней после перехода на смесь с полным гидролизом белка, однако иногда в тяжелых случаях может потребоваться внутривенное введение жидкости.…”
Section: к линические проявленияunclassified